Serum hepatitis B surface antigen correlates with fibrosis and necroinflammation: A multicentre perspective in China. Issue 9 (11th May 2018) - Zhang, P.; Du, HB.; Tong, GD.; Li, XK.; Sun, XH.; Chi, XL.; Xing, YF.; Zhou, ZH.; Li, Q.; Chen, B.; Wang, H.; Wang, L.; et al.
Summary: The kinetics of serum hepatitis B surface antigen (HBsAg) during the natural history of hepatitis B virus (HBV) infection has been studied, but the factors affecting them remain unclear. We aimed to investigate the factors affecting HBsAg titres, using data from multicentre, large‐sized clinical trials in China. The baseline data of 1795 patients in 3 multicentre trials were studied, and the patients were classified into 3 groups: hepatitis B early antigen (HBeAg)‐positive chronic HBV infection (n = 588), HBeAg‐positive chronic hepatitis B (n = 596), and HBeAg‐negative chronic hepatitis B (n = 611). HBsAg titres in the different phases were compared, and multiple linear progression analyses were performed to investigate the implicated factors. HBsAg titres varied significantly in different phases ( P = .000), with the highest (4.60 log10 IU/mL [10%‐90% confidence interval: 3.52 log10 IU/mL‐4.99 log10 IU/mL]) in patients with HBeAg‐positive chronic HBV infection. In all phases, age and HBV DNA were correlated with serum HBsAg level. In HBeAg‐positive chronic hepatitis B patients, a negative correlation between HBsAg titres and fibrosis stage was observed. Alanine amonitransferase or necroinflammatory activity was also correlated with HBsAg titres in HBeAg‐negative chronic hepatitis B patients. In conclusion, decreased HBsAg titres may be associated with advancing fibrosis in HBeAg‐positive chronic hepatitis B patients or increased necroinflammation in those with HBeAg‐negative chronic hepatitis B. Our findings may help clinicians better understand the kinetics of HBsAg and provide useful insights into the management of this disease.